Miraculous medicines and the chemistry of drug design - Keighley, Nathan (Boca Raton : CRC Press, 2020)
The subject of chemistry is widely acknowledged as being conceptually challenging, and regarded with a perceived elitism. This book aims to address this dilemma by breaking down the fundamentals of organic chemistry and its importance in medicine, so that readers with any or no background education in chemistry can access the material and gain an appreciation and understanding for the subject. The text is written in a clear and concise manner, using appropriate figures, to explain how the medicine we are so familiar with is designed and produced. Undergraduate students, medical and nursing students, and general audiences will benefit from the accessible format and enjoyable read. Key Features: User-friendly text dealing with the chemical sciences for the non-scientist Public understanding of science at the interface of biology and chemistry is in high demand The book serves to introduce organic chemistry and its relevance to medicine Describes the foundational principles of chemistry without losing the systematic rigor of the subject
OCLC-licensed vendor bibliographic record.
Keywords: Drugs -- Design; Pharmaceutical chemistry -- Research -- Methodology; SCIENCE / Chemistry / Organic; SCIENCE / Life Sciences / Biochemistry; MEDICAL / Biochemistry